Strategic Approach in the Development of Nakha Model for Malaria Elimination Management by Nakha Subdistrict Administrative Organization and Partnering of Nakha Subdistrict-level Network - ชูจันทร์ สุริโย; ภูมิรัตน์ อดิศักดิ์ (Journal of Health Science of Thailand, 2021)
This study aimed to develop Nakha model of malaria elimination management by Nakha Subdistrict Administrative Organization (SAO) in 2018 Public service delivery framework was applied for strategic approach to develop Nakha model that encompassed systems, mechanisms, steps and processes by which Nakha SAO could deliver community-based service system through partnering of Nakha Subdistrict-level network including Nakha Subdistrict Health Promoting Hospital (SHPH), Khaun Sai Ngam SHPH, Vector Borne Disease Control Unit 11.5.4 Kapoe, Suk Samran Hospital, and Suk Samran District Health Office. The strategic approach to Nakha model development encompasses 4 strategies such as active case finding, capacity building of surveillance and rapid response team and village health volunteers, malaria vector management, and surveillance and monitoring. This Nakha model development could achieve the concrete results of Nakha model that can establish the system and mechanisms for partnering of Nakha Subdistrict-level network and organization that can manage resources suited to control and eliminate malaria in defined Nakha SAO area of responsibility. More significantly, the model could build the capacity of malaria active case finding that was the mainstay of community services in a set of workplans of the action plan of vector-borne disease control personnel for fiscal years 2019-2021, and accordingly, it was directed by a panel of disease prevention and malaria control. This action plan has been put in place to fully integrate in Nakha SAO’s budget and public health plan of the local 4-year plan (2018-2021).